2019
DOI: 10.1175/bams-d-18-0030.1
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the HI-SCALE Field Campaign: A New Perspective on Shallow Convective Clouds

Abstract: Shallow convective clouds are common, occurring over many areas of the world, and are an important component in the atmospheric radiation budget. In addition to synoptic and mesoscale meteorological conditions, land–atmosphere interactions and aerosol–radiation–cloud interactions can influence the formation of shallow clouds and their properties. These processes exhibit large spatial and temporal variability and occur at the subgrid scale for all current climate, operational forecast, and cloud-system-resolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 67 publications
1
76
0
Order By: Relevance
“…One factor not considered in this study that affects the observed droplet number distribution is the variability in aerosol concentrations. Fast et al (2019) and Figure S8 show a large spatial gradient in aerosol number concentrations along the afternoon G-1 flight path on 30 August (Figure 1c). The highest concentrations greater than 8,000 cm 3 just east of the Central Facility are likely due to emissions from nearby refineries and a coal-fired power plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor not considered in this study that affects the observed droplet number distribution is the variability in aerosol concentrations. Fast et al (2019) and Figure S8 show a large spatial gradient in aerosol number concentrations along the afternoon G-1 flight path on 30 August (Figure 1c). The highest concentrations greater than 8,000 cm 3 just east of the Central Facility are likely due to emissions from nearby refineries and a coal-fired power plant.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the present simulations omit the effect of aerosols which could shift the simulated cloud droplet distribution to smaller sizes because of the Twomey effect (Twomey, 1977). As shown in Fast et al (2019) and Figure S8, there are strong gradients in particle concentrations along the G-1 flight legs on this day. Some clouds are embedded in high aerosol concentrations likely originating from refinery and power plant emissions near the SGP site, while other clouds are embedded in lower background aerosol concentrations.…”
Section: Cloud and Boundary Layer Propertiesmentioning
confidence: 99%
“…Even approaches like the LES ARM Symbiotic Simulation and observation workflow (LASSO) which are centered around intensive field measurements still adopt semi-idealized approaches using small domains which necessitate periodic boundary conditions (Fast et al, 2019). Super-parameterization has begun to allow a broader look at how an explicit representation of clouds couples to large-scale circulations (e.g., Parishani et al 2018), but still using individual sub-domains that remain small and idealized.…”
Section: Introductionmentioning
confidence: 99%
“…The HI‐SCALE field study was conducted during the 2016 growing season and included two aircraft intensive operations periods (IOPs) utilizing the Department of Energy's Gulfstream‐1 (G‐1) aircraft, one in the spring (24 April through 21 May) and one in the late summer/early fall (28 August to 24 September). Details of the HI‐SCALE field study and the aircraft payload are documented by Fast et al (2019). This study utilizes BB irradiance data collected using upward‐ and downward‐looking Delta‐T SPN1 pyranometers installed on the top and bottom of the fuselage.…”
Section: Data Sourcesmentioning
confidence: 99%